General profile of the Singapore Chinese gay community and their attitudes towards products or services catered to the gay community. - Ng, Alvin Kok Ping. (2008)
In our study, we built a general profile of the gay community in Singapore. Also, using the Theory of Reasoned Actions (TORA), we aim to find out this community’s attitudes towards products or services that are catered to them, how different social parties influence their attitudes and their likelihood to purchase.